Yurii Voronyi – a surgeon who was ahead of his time - Dubenko, D. (General Surgery, 2024)
The article outlines the historical milestones in the biography of the outstanding Ukrainian surgeon, Professor Yurii Voronyi, who was a disciple of Professor Yevhen Cherniakhivskyi. The study includes a compilation of historical records, archival sources, and other materials illustrating the life of Professor Voronyi. It highlights the professional and public achievements of Yurii Voronyi, particularly his participation in the struggle for Ukrainian independence between 1917 and 1921.